Kesesuaian Biaya Riil Terhadap Tarif INA-CBGS Pada Pasien Hipertensi di Rumah Sakit Umum Daerah Pandan Arang Boyolali Tahun 2017 - Isma Oktadiana; Oetari Oetari; Andayani Andayani (Fakultas Farmasi Universitas Setia Budi, 2019)
In Indonesia, the incidence of hypertension ranged from 6-15% and many patients are still not reached by health services, especially in rural areas. The research purposes to determine patterns of treatment of hypertension, the average cost of treatment, the factors that affect the total cost, and the cost of compliance with the real cost of the package INA-CBGs. The study was an observational cross-sectional study design according to the perspective of the hospital. Method of data collection was done in retrosfektif and data derived from quantitative data. Subjects were inpatients suffering from hypertension without comorbidities and hypertension with comorbid diabetes mellitus, heart failure and kidney failure. The results showed significant differences with the INA-CBG rates on total costs in outpatients differed significantly in 79 samples, while the real cost of Rp 335,145 was greater than the INA-CBGs rate of Rp. 181,400, while inpatients differed significantly in 63 samples at the grade I, grade 3, 2, 1 severity of Rp. Rp. , Rp. 1,438,069, Rp. 1,498,683, Rp. 2,000,685, the severity level II class 3 and class 1 was Rp. 1,540,134, Rp. 2,866,200, III and grade 1 III severity levels of Rp. 1,586,617 and Rp. 3,439,500. This difference shows a positive difference, where the total real cost is more.